Exploring Digital Signatures Secrecy in Web-Platform: Client-Side Cryptographic Operations - Silvano, Wellington Fernandes; Cabral, Gabriel; Mayr, Lucas; Schardong, Frederico; Custódio, Ricardo (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2024: Anais do XXIV Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg.2024.241786, 2024)
Online signature platforms confront critical security challenges, notably exposing sensitive documents to third-party applications. This paper presents a novel client-side cryptographic model that enhances document secrecy and key management by performing cryptographic operations within the user’s browser. By employing one-time certificates, our model eliminates document uploads, reducing the risk of leakage and private key compromise. Aligned with Claude Shannon’s information theory, our approach ensures robust secrecy while remaining compatible with existing digital signatures. Our implementation demonstrates practical performance, offers a significant advancement in secure digital signatures, addressing vulnerabilities in traditional web-based platforms.